PEMENUHAN HAK TERHADAP PENYANDANG DISABILITAS MENTAL DALAM MENERIMA PENDIDIKAN DARI PEMERINTAH DAERAH KOTA KABANJAHE: Fulfillment Of The Rights Of People With Mental Disabilities In Receiving Education From The Kabanjahe City Regional Government - Purba, Viona Abigail; Sulistyowati, Tri (AMICUS CURIAE, 2025)
Indonesian Laws and Regulations have regulated various rights of persons with disabilities in the field of education in Law Number 20 of 2003 concerning the National Education System, Law Number 8 of 2003 concerning Persons with Disabilities, and Law Number 23 of 2014 concerning the Government. Education in Law Number 20 of 2003 about the National Education System, is a programmed efforts to build a learning atmospgere and teaching and learning process that supports students in maximizing their potential.. Education is a right that everyone, including people with disabilities, must receive. The right to education for persons with disabilities is regulated in Article 10 of Law Number 8 of 2003 about persons with disabilities which states that persons with disabilities have the right to receive inclusive education. Inclusive educationreceived by persons with disabilities is within the authority and must be facilitated by the Central Government and Regional Government. For matters of educational affairs and fields, Law Number 23 of 2014 concerning regional government regulates that district/city Regional Governments have authority over basic education and the Central Government has authority over special schools which are assisted by the role of Regional Governments in providing facilities and monitoring the fulfillment of educational rights. So that it runs well,